2007
DOI: 10.1590/s0073-47212007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Diel density variation of amphipods associated with Sargassum beds from two shores of Ubatuba, Southeastern, Brazil

Abstract: ABSTRACT. Densities of mobile epifaunal assemblages associated with macrophytes are very variable during the day and the activity of visually-oriented predators is thought to have an important influence on this pattern. Here we compared densities of amphipods associated with a common brown alga, Sargassum stenophyllum (Phaeophyceae), at sites contrasting in water turbidity. We expected that diel variation of amphipods would occur in a shore with clear waters (Perequê), whereas no variation was expected in a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…Lamberto Beach is located in Enseada do Flamengo (23°30 0 S/45°07 0 W), and is classified as sheltered or semi-sheltered due to the barrier formed by Anchieta Island (Leite and Guth 2003;Leite et al 2007). The climate is tropical with rains distributed throughout the year (AF) and superhumid without dryness according to the Koeppen classification (SalatiFilho 2001).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Lamberto Beach is located in Enseada do Flamengo (23°30 0 S/45°07 0 W), and is classified as sheltered or semi-sheltered due to the barrier formed by Anchieta Island (Leite and Guth 2003;Leite et al 2007). The climate is tropical with rains distributed throughout the year (AF) and superhumid without dryness according to the Koeppen classification (SalatiFilho 2001).…”
Section: Study Areamentioning
confidence: 99%
“…Subtidal rocky shores in southeastern Brazil are dominated by species of the brown alga Sargassum (Széchy and Paula 2000). Praia do Lamberto specifically shows dominance by Sargassum stenophyllum, although other species may be present (Leite et al 2007). …”
Section: Study Areamentioning
confidence: 99%
“…These species are distributed in temperate, subtropical and tropical seas, mostly from 40°N to 20°S (for details of the species distribution see Winfield and Ortiz 2013). There are only three species of Paracaprella recorded from Brazilian waters: P. digitimanus (Quitete 1971), P. pusilla (Serejo 1998;Leite et al 2007;Dubiaski-Silva & Masunari 2008) and P. tenuis (Cunha et al 2008;Dubiaski-Silva & Masunari 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has shown that the composition and density of caprellids are influenced by structural elements of the algal substrate (phytal), such as ramification degree and thallii consistence (Masunari 1982, Dutra 1988, Dubiaski-Silva & Masunari 1995, Leite & Turra 2003, Leite et al 2007). These features regarding microhabitat occupation between caprellids species may increase interspecific competition (Aoki 1999).…”
Section: Introductionmentioning
confidence: 99%